Excessive fluoride exposure induces thymocyte apoptosis and impairs cell division: Roles of the PERK and IRE1 pathways. (1st August 2020) - Wei, Wei; Wang, Qian; Pang, Shujuan; Tan, Shiwen; Sun, Jing; Li, Mengdi; Wang, Shize; Sun, Dianjun
Highlights: Excessive fluoride inhibited division and induced apoptosis of thymocytes. Excessive fluoride induced activation of PERK and IRE1 signaling in thymocytes. PERK and IRE1 signaling induced by fluoride plays a key role in immunosuppression.